Pulsed laser annealed silicides formation for advanced MOS applications - Yudi, Setiawan. (2009)
The aim of this work is to investigate the laser-induced silicide and germanosilicide formation in detail. Three main aspects, which affect the laser-induced silicide or germanosilicide formation, will be evaluated. First of them is the effect of laser fluence and number of laser pulses. These directly affect the temperature generated in the sample, the melt and or reaction duration, and eventually the elemental mixing. Within this topic, several phenomena such as three-layered structure formation, enhanced elemental mixing, and laser-induced morphological alteration were observed. All of them are related to the fast heating, melting, and solidification processes which occurred during a non-equilibrium laser annealing (LA) process. Presence of regions with different elemental composition resulted in a variation of solidification velocities and its resultant microstructure. On the other hand, multiple-pulsed LA process is usually able to induce a more uniform elemental mixing and hence eliminating a multiple-layered structure which may form during single-pulsed LA process at a fluence higher than the melting threshold of the sample. In addition, it is found that LA might result in a formation of metastable structures such as twinning and supercell formation. Secondly the effect of substrate modification to induce the formation of a better germanosilicide/substrate interface is studied. It will be shown that by exploiting the difference in thermophysical and optical properties of materials, LA can be tailored such that it forms an atomically abrupt germanosilicide/substrate interface through a self-limiting melting phenomenon. The thermal confinement in the Si1-xGex based substrate has enable the heating process to be concentrated on the surface area of the sample. Lastly, evaluation on the effect of Pt alloying in enhancing the phase formation during LA of Ni(Pt) film on cond-Si1-xGex substrates has also been performed. The Si1-xGex substrate was fabricated through a SiGe condensation process. This process enables the formation of a Si1-xGex with high Ge content. Due to thermal confinement and a low Tm, the presence of high Ge content has caused the SiGe substrate to melt at a relatively low laser fluence. This increases the susceptibility of the sample to oxidation. It will be shown that adding alloying element such as Pt enables the reduction of oxygen intrusion to the germanosilicide and at the same time stabilize the phase formed in the film. Results such as better germanosilicide morphology, smoother interface and surface was observed in the sample with Pt alloying. In addition, the electrical properties of the LA silicide and germanosilicide will also be investigated in the last section